Left ventricular apical hydatid cyst - a rare case report - Thao, Le Nhat; Chuong, Pham Tran Viet; Thuan, Phan Quang; Linh, Pham Ngoc Phuong; Dao, Chau Hong; Vinh, Bui Duc An; Dinh, Nguyen Hoang (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Cardiac hydatid cyst is an extremely rare manifestation of cystic echinoccococis, but without prompt diagnosis and management, it can be fatal. Despite the absence of standardized guidelines, an early, complete surgical removal in conjunction with anthelmintic therapy plays a central role and is associated with an excellent prognosis. We report an indigenous case of left ventricular apical hydatid cyst in a 75 - year - old female who presented with atypical symptoms including abnormal fatigue and increasing exercise intolerance. Although serological tests were negative, imaging modalities revealed a 36 x 30 mm oval structure in the left ventricular apex, suggesting a type I hydatid cyst. A single encapsulated cyst was surgically removed through a median sternotomy under cardiopulmonary bypass. Histopathological analysis confirmed a hydatid cyst, and Echinococcus ortleppi was identified. The patient was discharged without incident and was prescribed 3 cycles of Albedazole.